Necessary and Sufficient Conditions in Inverse Scattering Problem on the Axis for the Triangular 2 × 2 Matrix Potential - Zubkova, E. I.; Rofe-Beketov, F. S. (Журнал математичної фізики, аналізу, геометрії, 2009)
The characteristic properties of the scattering data for the Schrödinger operator on the axis with a triangular 2 × 2 matrix potential are obtained. A difference between the necessary and sufficient conditions for solvability of ISP under consideration, contained in the previous works of the authors, is eliminated. Mathematics Subject Classification: 47A40, 81U40.